The Effect of Rejuvenation Methods on the Growth of Immature Oil Palms (Elaeis guineensis Jacq.) and Bulk Density - Muhammad Bonie; Ida Nursanti (Jurnal Prajaiswara, 2026)
Introduction/Main Objectives: Rejuvenation method (replanting) in oil palm plants is the process of replacing old or unproductive plants with new, superior plants so that plantation productivity remains high and sustainable. The choice of rejuvenation method depends, among others, on the condition of the plant and the condition of the land. This study aims to determine the growth of immature oil palm and bulk density in several rejuvenation methods. Research Methods: The materials used are 2-year-old Tenera variety oil palm plants from Sampoerna Agro. The tools used are plastic plates, paint, cameras, stationery, meters, Global Positioning System, Dial thicknesses, sample rings and Krisbow light meters. The design used in this study is a Randomized Block Design  with one treatment factor, namely the oil palm rejuvenation method, namely L0: new land clearing method, L1: insertion planting pattern (underplanting), L2: total uprooting planting pattern. Each treatment was divided into three groups, with 10 plant samples taken from each group. Observed parameters were plant height, stem circumference, leaf thickness, soil density, and light intensity. Observational data were analyzed using ANOVA. If significant differences were obtained, the DNMRT test was performed at the α level of 5%. Finding/Results: The rejuvenation method significantly affected plant height and stem circumference growth. The interplanted oil palm rejuvenation method resulted in the highest average increase in stem height, while the highest growth in stem circumference and leaf thickness was found with the new land clearing method. The new land clearing method had the lowest bulk density, at 1.32 g/cm3.